Design and Fabrication of Polymer-Based Asymmetric Waveguide Coupler Utilizing Injection Moulding Process - F. R. M., Romlay; Mohd Shafiq, Mat Ghazali; Luqman, Ismail (Knowledge Transfer Programme, Universiti Sains Malaysia, 2017)
Manufacture the plastic optical fiber (POF) is the key issue in this technology transfer program. Accelerate the manufacturing process of POF is the objective in this program. The design and modelling of an asymmetric waveguide couplers based on optical glue Epoxy OG142 is presented. The design of the asymmetric coupler is based on asymmetric Y-junction splitter using tap-off ratio (TOFR) technique. This asymmetric design was achieved by varying the size of the tap line while the bus line was fixed at 1 mm size. A Y-branch and the 1x2 asymmetric couplers with different taper sizes have been designed using CAD tool and ray traced using non-sequential ray tracing. Plastic injection moulding procedure as the knowledge transfer methodology set is set up to manufacture the coupler. The designed TOFR for the 1x2 asymmetric coupler varies from 23% to 50% for tap line width of 300 um to 1000 um. Ray tracing models of various coupler designs showed a linear relationship between the tap-off ratio (TOFR) and the waveguide tap width.